Дослідження багатошарового поселення Іванків 3 у 2014—2015 рр. - Чміль, Л.В.; Козюба, В.К.; Оленич, А.М. (Археологія і давня історія України, 2019)
Статтю присвячено публікації результатів дослідження об'єкта другої половини XIII — початку
XIV ст. на багатошаровій пам'ятці Іванків 3, розташованій в Іванківському р-ні Київської обл. The paper deals with publication of the results of
investigations of the object of the second half of 13th — early 14th centuries on the multilayer site Ivankiv 3 situated
in Ivankiv district of the Kyivan region. Northern districts of Kyivan Polissia are archaeologically little
known ones. Since 2013 the archaeological investigations have been carried out there by the authors. During last
5 years 25 monuments were inspected. The settlement Ivankiv 3 is distinguished among them. It is multilayer
monument in the flood-lands of the Teteriv river left bank, among Zaprudka village and Ivankiv town. It is
situated on the dune hill. The authors found flinty tools of the Mesolithic—Neolithic, ceramics of the Bronze and
the Early Iron Ages, the 11th—12th and 16th—17th centuries on the settlement area. However the rectangular
shaped object of the second half of 13th — early 14th century excavated in the years 2014—2015 is the most interesting.
It was 3.1 × 1.8 meters long and 0.95 meter deep. Perhaps it was household building crushed by a
fire. It was filled with black soil mixed with carbons, fired clay and animal bones. There were a number of
materials in the object. Ceramics is presented by pots mainly. The shapes of their rims are of the post-Mongolian
period. Some of them are with spots of glaze that demonstrate a glaze production at that time. There are
also fragments of bowls, covers and brown glazed jugs. Among other materials there were a small spin-wheel of
pyrophyllite and fragments of that mineral, iron hook, two bits of glass bracelets and two grindstones. The animal
bones from the object belonged to 5 pigs, 2 goats / sheeps, a cow, 2 beavers and a fish. The slags of iron production were found on the area as well. The investigation of the site is very important to study the regional history in the post-Mongolian period.